Operation Bounce House [large type] - Dinniman, Matt (Random House Large Print Publishing, 2026)
"All colonist Oliver Lewis ever wanted to do is run the family ranch with his sister, maybe play a gig or two with his band, and keephis family's aging fleet of intelligent agriculture bots ticking aslong as possible. As a fan of Earth television and culture, he figures it will be a good thing when the transfer gate finally opens allthe way and restores instant travel and full communication between Earth and his planet, New Sonora. But there's a complication: even though the settlers were promised they'd be left in peace, Earth's government now has other plans. The colossal Apex Corporation is hiredto commence an 'eviction action.' But maximizing profits will always be Apex's number one priority"--